1984
DOI: 10.1037/0022-3514.46.3.561
|View full text |Cite
|
Sign up to set email alerts
|

Friendship choice and performance: Self-evaluation maintenance in children.

Abstract: The present study examined the interrelations among performance in school, friendship choices in the classroom, and the importance of various school-related' activities for a child's self-definition. Children named as friends those classmates whose performance (both actual and distorted) was better than their own on irrelevant activities and somewhat inferior to their own on relevant activities. There was also a striking similarity effect. Friends' overall performance was highly similar to the subject's own ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
4
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 16 publications
5
70
4
1
Order By: Relevance
“…It is noteworthy that researchers have defined the "personal consequence" of attributes differently. In some studies, the importance of the attribute to the individual has been considered (e.g., Tesser et al, 1984); qualitative research (e.g., Fordham & Ogbu, 1986;Peshkin, 1991) suggests that how strongly the adolescent is invested in the attitude or behavior is important for the selection of similar friends. In the current investigation, the strength of adolescents' academic orientations, ethnic identity, and degree of substance use were points of focus.…”
Section: Individual Contextual and Relationship Moderators Of Frienmentioning
confidence: 99%
“…It is noteworthy that researchers have defined the "personal consequence" of attributes differently. In some studies, the importance of the attribute to the individual has been considered (e.g., Tesser et al, 1984); qualitative research (e.g., Fordham & Ogbu, 1986;Peshkin, 1991) suggests that how strongly the adolescent is invested in the attitude or behavior is important for the selection of similar friends. In the current investigation, the strength of adolescents' academic orientations, ethnic identity, and degree of substance use were points of focus.…”
Section: Individual Contextual and Relationship Moderators Of Frienmentioning
confidence: 99%
“…A first component of Tesser's model is relevant to the information manipulation portion of our hypothesis. When a comparison domain is of importance (and thus comparative information is potentially threatening), individuals can respond to comparisons by distorting perceptions of their own performance on an activity in ways that make the performance seem more positive (Tesser, Campbell, & Smith, 1984). Moreover, individuals can change their perceptions of the other person in ways that make the other person appear less positive relative to the self (Tesser & Campbell, 1982).…”
Section: The Motivated Manipulation Hypothesismentioning
confidence: 99%
“…Social comparison is the key factor during the process. Tesser et al (1984) explored the influence of social comparisons on the choice of friends and examined whether people would choose friends who performed better than they did or who performed poorly on a major dimension. They found that children would make friends with people who are somewhat inferior in their important fields.…”
Section: Dishonestymentioning
confidence: 99%